PENGARUH STANDAR OPERASIONAL PROSEDUR, GAYA KEPEMIMPINAN, DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN PT. SASA INTI MINAHASA SELATAN: PENGARUH STANDAR OPERASIONAL PROSEDUR, GAYA KEPEMIMPINAN, DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN PT. SASA INTI MINAHASA SELATAN - Andani, Yuli; S.L.H.V. Joyce Lapian; Frederik G. Worang (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Increasing industrial competition requires companies to improve employee performance through effective human resource management. Standard Operating Procedures (SOPs), leadership style, and work culture are important factors that are presumed to influence employee performance. This study aims to analyze the effect of SOPs, leadership style, and work culture on employee performance at PT Sasa Inti Minahasa Selatan, particularly in the Finished Goods Warehouse division. This research employed a quantitative approach using a survey method involving 60 respondents selected through a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that SOPs, leadership style, and work culture partially have a positive and significant effect on employee performance. Furthermore, these three variables simultaneously have a significant effect on employee performance. The Adjusted R Square value of 0.602 indicates that 60.2% of the variation in employee performance can be explained by SOPs, leadership style, and work culture, while the remaining 39.8% is influenced by other factors outside this study. These findings confirm that consistent implementation of SOPs, effective leadership, and a supportive work culture play an important role in improving employee performance. Keywords: Standard Operating Procedures, Leadership Style, Work Culture, Employee Performance.